SPE International Conference and Exhibition on Health, Safety, Security, Environment, and Social Responsibility 2018
DOI: 10.2118/190563-ms
|View full text |Cite
|
Sign up to set email alerts
|

Human Performance and Safety Culture Initiatives Transform Safety Performance

Abstract: At the time of acquiring a remote greenfield gas development in 2013, the project's total recordable injury rate (TRIR) for the site development phase was 2.0. Though this rate was considered competitive for the industry sectors in which the local contractors generally worked, it was considerably higher than that prevailing in the oil and gas industry and did not meet corporate expectations. Several potentially serious near misses provided additional impetus for action. Six staged programs were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…For example, one early occupational accident study revealed that more than 500 workers per year died with a further 1500 severe and non-fatal incidents having occurred in Allegheny County Pennsylvania. According to Hoffmann, et al [2], Malaysia's oil and gas industry is a major contributor to the national economy. Malaysia's national oil company is no exception.…”
Section: Introductionmentioning
confidence: 99%
“…For example, one early occupational accident study revealed that more than 500 workers per year died with a further 1500 severe and non-fatal incidents having occurred in Allegheny County Pennsylvania. According to Hoffmann, et al [2], Malaysia's oil and gas industry is a major contributor to the national economy. Malaysia's national oil company is no exception.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the US Department of Energy introduced HPI guidance books as references to enhance HPI through concepts and tools [9,10]. Nowadays, industries widely use HPI to improve safe work practices [28][29][30][31].…”
Section: Hpi Implementationmentioning
confidence: 99%
“…The most critical element of integrating HPI into organizations is leadership because leadership can direct the organization in deploying the whole process [10,28,30]. Fostering HPI principles requires shifting leadership thinking through multiple leadership engagements, dialogues, and discussions [7,21,29]. Leadership plays a vital role in deployment, implementation, and stewardship when applying HPI principles.…”
Section: Hpi Implementationmentioning
confidence: 99%